Recombinant inbred systems can advance research in behavioral ecology - Gini, Beatrice; Hager, Reinmar (Frontiers in Genetics, 2012)
Recombinant inbred (RI) systems such as the BXD mouse family represent a population with defined genetic architecture and variation that approximates those of natural populations. With the development of novel RI lines and sophisticated methods that conjointly analyze phenotype, gene sequence and expression data, RI systems such as the BXD are a timely and powerful tool to advance the field of behavioural ecology. The latter traditionally focused on functional questions such as the adaptive value of behaviour but largely ignored underlying genetics and mechanisms. In this perspective, we argue that using RI systems to address questions in behavioural ecology and evolutionary biology has great potential to advance research in these fields. We outline key questions and how they can be tackled using RI systems and BXD in particular. The unique opportunity to analyze genetic and phenotypic data from studies conducted in different laboratories and at different times is a key benefit of RI systems and may lead to the way to a better understanding of how adaptive phenotypes arise from genetic and environmental factors.